Effect of apigetrin in pseudo-SARS-CoV-2-induced inflammatory and pulmonary fibrosis in vitro model - Hengmin Han; Jung-Eun Kim; Hyo-Jeong Lee (Scientific Reports, 2024)
Abstract SARS-CoV-2 has become a global public health problem. Acute respiratory distress syndrome (ARDS) is the leading cause of death due to the SARS-CoV-2 infection. Pulmonary fibrosis (PF) is a severe and frequently reported COVID-19 sequela. In this study, an in vitro model of ARDS and PF caused by SARS-CoV-2 was established in MH-S, THP-1, and MRC-5 cells using pseudo-SARS-CoV-2 (PSCV). Expression of proinflammatory cytokines (IL-6, IL-1β, and TNF-α) and HIF-1α was increased in PSCV-infected MH-S and THP-1 cells, ARDS model, consistent with other profiling data in SARS-CoV-2-infected patients have been reported. Hypoxia-inducible factor-1 alpha (HIF-1α) siRNA and cobalt chloride were tested using this in vitro model. HIF-1α knockdown reduces inflammation caused by PSCV infection in MH-S and THP-1 cells and lowers elevated levels of CTGF, COLA1, and α-SMA in MRC-5 cells exposed to CPMSCV. Furthermore, apigetrin, a glycoside bioactive dietary flavonoid derived from several plants, including Crataegus pinnatifida, which is reported to be a HIF-1α inhibitor, was tested in this in vitro model. Apigetrin significantly reduced the increased inflammatory cytokine (IL-6, IL-1β, and TNF-α) expression and secretion by PSCV in MH-S and THP-1 cells. Apigetrin inhibited the binding of the SARS-CoV-2 spike protein RBD to the ACE2 protein. An in vitro model of PF induced by SARS-CoV-2 was produced using a conditioned medium of THP-1 and MH-S cells that were PSCV-infected (CMPSCV) into MRC-5 cells. In a PF model, CMPSCV treatment of THP-1 and MH-S cells increased cell growth, migration, and collagen synthesis in MRC-5 cells. In contrast, apigetrin suppressed the increase in cell growth, migration, and collagen synthesis induced by CMPSCV in THP-1 and MH-S MRC-5 cells. Also, compared to control, fibrosis-related proteins (CTGF, COLA1, α-SMA, and HIF-1α) levels were over two-fold higher in CMPSV-treated MRC-5 cells. Apigetrin decreased protein levels in CMPSCV-treated MRC-5 cells. Thus, our data suggest that hypoxia-inducible factor-1 alpha (HIF-1α) might be a novel target for SARS-CoV-2 sequela therapies and apigetrin, representative of HIF-1alpha inhibitor, exerts anti-inflammatory and PF effects in PSCV-treated MH-S, THP-1, and CMPVSC-treated MRC-5 cells. These findings indicate that HIF-1α inhibition and apigetrin would have a potential value in controlling SARS-CoV-2-related diseases.